INDIAN ASTRONOMY INFORMATION CENTERS' INFORMATION-SEEKING PATTERNS IN LIBRARIES - Rhuhi Fatma, Gazala (International Journal of Multidisciplinary Research and Studies, 2020)
Information-seeking behavior is an essential component in the designing and developing of need-based information centers for meeting the information requirements of users. The undertaken study describes the information needs and information-seeking behavior of post-graduate students and research scholars of Banaras Hindu University, Varanasi, Uttar Pradesh. The main objective of this research study is to analyze the information-seeking pattern of students in the social sciences stream. The survey was conducted to look more closely at specific areas of the study for an in-depth examination of trends and patterns in seeking information. It is found that almost all students used to get information through the Internet but they prefer print material over digital resources for study purposes. They face a lot of difficulties and obstacles to accessing those electronic and print resources. Therefore, orientation programs and users‟ education programs are imperative to give them information on library services and activities. This study can be helpful for students as well as for teachers, librarians, and mentors who provide information to the students and researchers